Impact of the United States-China Trade War Through Indonesian Macroeconomic Studies on the LQ-45 Stock Index - Maulana Dhiyahul Haq; Nora Ria Retnasih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the impact of the trade war between the United States and China through Indonesian macroeconomic studies on the LQ-45 stock index in the short and long term. The research method used in this study is a quantitative method. Data collection in this study was obtained online in the form of data on several macroeconomic subsectors. The analysis method used in this study is the Vector Error Correction Model (VECM) to examine the impact caused in the short and long term. The results of this study show that in the short term, only the LQ-45 variable has a self-influence, while in the long term, all variables have an impact on LQ-45. Positive effects were observed from the FED Rate, and Exports, while negative effects were seen from the BI Rate, CNY Rate, USD Rate, and Imports.